Effects of Remittances on Poverty among Rural Households in Nigeria - Olowa, Olatomide Waheed; Awoyemi, Taiwo Timothy; Shittu, Musediku Adebayo a; Olowa, Omowumi Ayodele (European Journal of Sustainable Development, 2013)
Poverty in Nigeria is more prevalent in therural sector due to dwindling and inequitabledistribution of real income. Remittances (money and goods sent by migrants to relativesback home) can be poverty reducing. However,the extent to which remittances affectpoverty and income inequality has not been adequately documented inNigeria.This paperuses a large, nationally-representative household survey to analyse the impact of domesticremittances (from Nigeria) and foreign remittances (from African and other countries) onpoverty in rural Nigeria. The socioeconomic characteristics showed that on the average,households that received foreign remittanceshad older heads (61.7± 19.7 years), smallerhousehold size (4.0 ± 2.5), bigger land size(18.53±26.5 ha), higherliteracy rate (0.50 ±0.5) and non-poor (0.08 ±0.3) with higher annual per capita expenditure (?111,768 ±?179,868). Poverty analysis showed that both types of remittances reduce the level,depth and severity of poverty in rural Nigeria.However, the size of the poverty reductiondepends on how poverty is being measured. The paper finds that poverty is reduced morewhen domestic, as opposed to foreign remittances are included inhousehold income, andwhen poverty is measured by the more sensitive poverty measures: poverty gap andsquared poverty gap. At a poverty line of?23,733 per annum, a 10%increase in domesticremittances decreased Poverty Incidence(PI), Poverty Gap (PG) and Squared PovertyGap (SPG) by 1.80%, 1.60% and 1.60% while10% rise in foreign remittances reducedpoverty incidence (PI), Poverty gap (PG) and Squared poverty gap (SPG) by 0.86%,0.62% and0.62% respectively in rural Nigeria. Across GPZs, While 10% increase inforeign remittances reduced PI (-0.88%) in North-Central (NC) it had no effect in NE(0.00%). Same increase in domestic remittances reduced PI, PG, SPG most in the SS (-0.29%, -1.85% and -0.75%) and leastin NE (-0.09%, -0.82% and -0.22%